CO26 | Relationship between SMAD3 variants and non-aortic cardiovascular features (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: SMAD3 gene encodes a component of the TGFβ-signaling system and is associated with Loeys-Dietz syndrome (LDS) and natural history for aortic dissection at smaller aortic diameter and arterial aneurysms. In this study we have explored the relationship between rare genetic variants identified in SMAD3 gene and non-aortic cardiovascular features in subjects attending the Regional Referral Centre for Marfan Syndrome and Related Disorders (Careggi Hospital, Florence) for differential diagnosis.